SOSIALISASI PEMBUATAN JARINGAN LOKAL DI SMK TRI DHARMA 3 KOTA BOGOR - Irfan Maulana; Abdullah Al Ghifari Abdullah Al Ghifari; Aditya Rizqiandri Saputra Aditya Rizqiandri Saputra; Alif Nur Qalbani Alif Nur Qalbani; Arief Nur Febrianto Arief Nur Febrianto; Gilang Nur Dwiansyah Gilang Nur Dwiansyah; Hendrik Louis Mahdi Hendrik Louis Mahdi; Muhammad Alfito Risky Pratama Muhammad Alfito Risky Pratama; Muhammad Rizal Muhammad Rizal (Abdi Jurnal Publikasi, 2023)
In this journal, we explain about the socialization of making a local network based on Cisco Packet Tracer at Tri Dharma 3 Vocational School, Bogor City. We start by providing background on the importance of understanding computer network technology in today's digital era, and why we chose to use Cisco Packet Tracer as a learning tool. Next, we explain the socialization process that we carried out, from planning and preparation to the implementation of the activity. We also provide a description of the material that we convey during the outreach, including an explanation of how to use Cisco Packet Tracer and how to create a local network using Cisco Packet Tracer software. In addition, we also provide an evaluation of the socialization activities that we carry out, including feedback from students who take part in the socialization. We conclude that the socialization of making a local network based on Cisco Packet Tracer at Tri Dharma 3 Vocational School, Bogor City can be considered a success because students can understand the material provided and show a high interest in computer network technology. We also hope that this activity can be one of the efforts to improve the quality of information technology education in schools. Keywords : Information technology, local network, digital era.